Approach to trans population in Nursing education (Research, Society and Development, 2022)
Objective: To explore the insertion of health promotion of the trans population in the curricula of different nursing courses. Methodology: This is an exploratory documentary research, which used as a source of information the documents of public archives of written origin, these being the curricular grids and the Course Pedagogical Project. Results: The universities of the State of São Paulo, despite being the state with the highest rate of murders in the trans population, the approach of this theme in the higher education institutions of the nursing course is still scarce, since only two of those classified in Enade 3, 4 and 5 present a specific discipline for this content. It is clear that the current training does not yet demonstrate the importance of offering a discipline aimed at the trans population. Conclusion: The research showed that nursing education in this perspective still has some weaknesses, that one of the limitations of the study was to find updated menus, because of the one hundred and twelve selected universities, only nine are foreseen in the PPCs and address the proposed theme.